Neutrophil to Lymphocyte Ratio on Admission to Predict Mortality of COVID-19 Elderly Patients - Fenty Fenty; Usi Sukorini (Indonesian Association of Clinical Pathologist and Medical laboratory, 2024)
Severe Acute Respiratory Syndrome Corona Virus Disease-2 (SARS-COV-2) is the cause of COVID-19, which led to a global pandemic and high mortality rate, especially in elderly patients. The declining immune system in elderly patients and comorbid diseases lead to more severe symptoms and an increased mortality rate. Many studies have shown that a high Neutrophil-Lymphocyte Ratio (NLR) value can predict the severity and mortality of COVID-19. However, studies on NLR in elderly patients in Indonesia have rarely been conducted. This study aimed to determine the role of NLR on admission as a mortality predictor in COVID-19 elderly patients who underwent in-hospital treatment. This research is an analytical observational study with a retrospective cohort method conducted in Bethesda Hospital, Yogyakarta, Indonesia. The research subjects were selected from July 2020 to October 2021 according to inclusion and exclusion criteria. Inclusion criteria were all elderly COVID-19 patients with an age limit of > 60 years old who had complete hemogram data on admission, demographic data, diagnostic criteria, types of comorbid diseases, and patient outcomes (survivor or non-survivor). The exclusion criteria were elderly COVID-19 patients with incomplete Electronic Medical Records (EMR). This study found 122 elderly patients with COVID-19 with a mortality rate of 30.33%. The result showed that NLR on admission significantly increased significantly in the non-survivor group compared to the survivor group. Multivariate Cox regression analysis presented severity (RR: 5.181; CI 1.662-16.154; p=0.005), comorbid diabetes mellitus (RR: 2.829; CI: 1.115-7.178), NLR > 6.04 (RR: 6.356; CI: 2.428-16.639) and other comorbid, namely thyroid, autoimmune, cancer, and anemia (RR: 15.836; CI: 1.841-136.234; p=0.012) as factors of mortality in hospitalized elderly patients.